2010
DOI: 10.1681/asn.2009121274
|View full text |Cite
|
Sign up to set email alerts
|

Barttin Activates ClC-K Channel Function by Modulating Gating

Abstract: Barttin is an accessory subunit that modifies protein stability, subcellular distribution, and voltagedependent gating of ClC-K chloride channels expressed in renal and inner ear epithelia. ClC-K channels are double-barreled channels with two identical protopores that may be opened by individual or common gating processes. Using heterologous expression in mammalian cells and patch-clamp recordings, we studied the effects of barttin on gating of rat ClC-K1 and human ClC-Ka. In the absence of barttin, rClC-K1 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
100
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 29 publications
(37 reference statements)
2
100
0
Order By: Relevance
“…The rodent CLC-K isoform rClC-K1 is active also in the absence of barttin and exhibits fast protopore and slow common gating steps. Co-expression of rClC-K1 and barttin results in a permanently open common gate (27,45). Although such effect on the common gate of human CLC-K channel function cannot be directly demonstrated, we recently demonstrated that hClC-Ka/barttin channels exhibit an open common gate (27).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The rodent CLC-K isoform rClC-K1 is active also in the absence of barttin and exhibits fast protopore and slow common gating steps. Co-expression of rClC-K1 and barttin results in a permanently open common gate (27,45). Although such effect on the common gate of human CLC-K channel function cannot be directly demonstrated, we recently demonstrated that hClC-Ka/barttin channels exhibit an open common gate (27).…”
Section: Discussionmentioning
confidence: 90%
“…This mutation endows rClC-K1 with pronounced barttin-dependent changes in time-and voltage dependence (Fig. 5, A-C) (6,27).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations